Personalized fundraising: A field experiment on threshold matching of donations - Maja Adena; Steffen Huck (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We study a form of threshold matching in fundraising where donations above a certain threshold are topped up with a fixed amount. We show theoretically that threshold matching can induce crowding in if appropriately personalized. In a field experiment, we explore how thresholds should be chosen depending on past donations. The optimal choice of thresholds is rather bold, approximately 75% above past donations. Additionally, we explore how thresholds should be set for new donors as a function of their personal characteristics and demonstrate the benefits of personalization as opposed to setting a general threshold that applies to all recipients of a fundraising call.
Keywords: C93; D64; D12; 330; Charitable giving; field experiments; matching donations; personalization